Isosteric ribavirin analogues: Synthesis and antiviral activities. Issue 1 (1st January 2018) - Zhurilo, Nikolay I.; Chudinov, Mikhail V.; Matveev, Andrey V.; Smirnova, Olga S.; Konstantinova, Irina D.; Miroshnikov, Anatoly I.; Prutkov, Alexander N.; Grebenkina, Lyubov E.; Pulkova, Natalya V.; Shvets, Vitaly I.
Graphical abstract: Abstract: The novel isosteric ribavirin analogues were synthesized by two different ways. Some of them showed significant antiviral action against hepatitis C virus (HCV), herpes simplex (HCV-1) and influenza A virus comparable to that of ribavirin itself. The data obtained confirm the proposed theory of the ribavirin possible antiviral activity mechanism related with bioisosterism.